Confirmation and characterization of cyhalofop-butyl–resistant Chinese sprangletop (Leptochloa chinensis) populations from China. Issue 3 (14th May 2020) - Peng, Yajun; Pan, Lang; Liu, Ducai; Cheng, Xiaomei; Ma, Guolan; Li, Sifu; Liu, Xueyuan; Wang, Lifeng; Bai, Lianyang
Abstract: Chinese sprangletop [ Leptochloa chinensis (L.) Nees] is one grass weed severely affecting rice ( Oryza sativa L.) growth in paddies in China. Cyhalofop-butyl is the main herbicide used to control grass weeds in Chinese paddy fields, especially for controlling L. chinensis ; however, L. chinensis has evolved resistance to cyhalofop-butyl due to continuous and extensive application. To investigate cyhalofop-butyl resistance levels and mechanisms in L. chinensis in some of the Chinese rice areas, 66 field populations were collected and treated with cyhalofop-butyl. Of these tested populations, 10 showed a high level of resistance to cyhalofop-butyl; the 50% effective dose ranged within 108.4 to 1, 443.5 g ai ha −1 with resistance index values of 9.1 to 121.8 when compared with the susceptible population. Acetyl-coenzyme A carboxylase genes ( ACCase ) of susceptible and all 10 resistant populations were amplified and sequenced. Among them, Ile-1781-Leu, Trp-2027-Cys, Trp-2027-Ser, and Ile-2041-Asn mutations were found in five resistant populations. No known resistance-related mutations were found in the other five resistant populations, indicating that resistance to cyhalofop-butyl in these populations was likely to be endowed by non–target site resistance mechanisms. Notably, the Ile-1781-Leu and Trp-2027-Cys substitutions have previously been reported, but this is the first report of Trp-2027-Ser and Ile-2041-Asn mutations in L. chinensis . Furthermore, three derived cleaved amplified polymorphic sequence methods were developed to rapidly detect these mutations in L. chinensis .